2006
DOI: 10.1002/bsl.718
|View full text |Cite
|
Sign up to set email alerts
|

Psychological processes and paranoia: implications for forensic behavioural science

Abstract: Paranoid delusions have recently become the focus of empirical research. In this article, we review studies of the psychological mechanisms that might be involved in paranoid thinking and discuss their implications for forensic behaviour science. Paranoia has not been consistently associated with any specific neuropsychological abnormality. However, evidence supports three broad types of mechanism that might be involved in delusional thinking in general and paranoia in particular: anomalous perceptual experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 116 publications
3
34
0
1
Order By: Relevance
“…In fact; it is reported that those who are subjected to hearing loss in old age suffer from paranoid psychosis more than the normal population [35] [36]. Most of the widespread epidemiological studies undertaken lately support -especially-the correlation between audio visual perception disorders and psychiatric disorders [7] [19] [45].…”
Section: Discussionmentioning
confidence: 99%
“…In fact; it is reported that those who are subjected to hearing loss in old age suffer from paranoid psychosis more than the normal population [35] [36]. Most of the widespread epidemiological studies undertaken lately support -especially-the correlation between audio visual perception disorders and psychiatric disorders [7] [19] [45].…”
Section: Discussionmentioning
confidence: 99%
“…h) Az önértékelés csökkenése [14] szintén lényeges lehet, a társas életben a biztos tájékozódást vesztő, saját értékeit minimalizáló, az értéktelenség hamis érzésével vergődő és aggódó/szorongó lélek jó táptalaj a tévesz més gondolkodás kifejlődésére. Az önértékelés/önbe csülés megromlása (az önbecsülés önbecsmérlésbe át csapása) depresszióban különösen gyakori.…”
Section: A Paranoia Kialakulásának Tényezőiunclassified
“…Genetic studies have similarly been unable to disentangle delusional disorder from paranoid personality disorder (Winokur 1985), although it now appears that both disorders are probably genetically distinct from schizophrenia (Asarnow 2001;Cardno 2006). This diagnostic problem can be viewed as part of a wider debate about the boundaries of psychosis, and the resurgent idea that psychotic symptoms are best conceptualised as dimensional phenomena on continua with normal experiences (Claridge 1997;van Os 2000;Bentall 2006). In his classic paper, Strauss (1969) suggested four criteria for determining the threshold into clinical psychotic illness: degree of conviction regarding the objective reality • Others (Claridge 1997) have emphasised that the key distinction is not simply the level of symptoms but rather their effect on day-to-day coping abilities, i.e.…”
Section: Delusional Disordermentioning
confidence: 99%
“…People with high levels of paranoid thinking have an externalising, personal attributional bias: a tendency to explain negative events in their life by blaming others rather than reflecting on their own potential contribution to circumstances (Bentall 2001(Bentall , 2006. The normal self-serving bias, whereby negative events are attributed to external circumstances, is exaggerated and distorted (Campbell 1999), being skewed towards other people and their supposed malevolent intent.…”
Section: Cognitive Biasesmentioning
confidence: 99%
See 1 more Smart Citation